Bone Mineral Density, Body Composition, and Mineral Homeostasis Over 24 Months in Urban South African Women With HIV Exposed to Antiretroviral Therapy - Hamill, Matthew M (JBMR Plus, 2020)
Human immunodeficiency virus‐ (HIV‐) infection and antiretroviral therapy (ART) exposure are associated with bone loss. African data are limited despite the region's HIV burden. Of 247 ART‐naïve, premenopausal, urban, black African women aged 33.9 ± 6.6 years from Soweto, South Africa, measured at baseline, 110 underwent anthropometry, DXA, and blood and urine collections at 12 and 24 months; 39 were HIV‐negative (Nref), 28 were people with HIV (PWH) not ART‐exposed for the duration of the study (ART‐N), and 43 were PWH who were ART‐exposed within the first 12 months (ART‐Y). At baseline, the ART‐Y group had lower BMI and fat mass than the Nref group. Within 12 months of ART initiation, areal bone mineral density (aBMD) had decreased at the lumbar spine and at the whole body less head, despite increased weight, and hip aBMD had not increased in line with the Nref group. There was no evidence of further bone changes between 12 and 24 months. By 24 months, the ART‐Y women had gained weight and fat mass, but remained lighter with less fat than the Nref women. ART initiation normalized the low serum albumin of the ART‐Y group at baseline, but was associated with elevated bone turnover markers at 12 and 24 months. Vitamin D status and renal phosphate handling were normal. ART‐N had similar aBMD and other characteristics to the Nref group throughout, except unlike the Nref group, weight and fat mass did not increase and serum albumin decreased. This study in African women of childbearing age demonstrated that the bone loss that had occurred in these PWH after ART initiation did not continue after 12 months and that bone loss did not occur in ART‐unexposed PWH over 2 years. At 24 months, despite gains in weight and fat mass, ART‐exposed women remained lighter, with lower aBMD, fat mass, and higher bone turnover than women without HIV. More studies are required to establish if the bone loss and fat gain reverse, stabilize, or continue with further ART exposure, particularly during and after menopause. © 2020 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.